PROTECTIVE EFFECT OF MURRAYA KOENIGII ON LIPID PEROXIDE FORMATION IN ISOLATED RAT LIVER HOMOGENATE - VANDANA GUPTA; MUKTA SHARMA (International Journal of Pharma and Bio Sciences, 2010)
Restrictions on the use of synthetic antioxidants are being imposed because of their toxic properties. The present study is the continuation of a program aimed at investigation on antioxidant activity of extracts from medicinal plants and to identify alternative natural and safe sources of food antioxidant especially from plant origin. In this report the anti-peroxidative effect of alcoholic extract of Murraya koenigii has been studied in rat liver homogenate. Ferrous sulphate has been used as inducer to induce lipid per oxidation. On the basis of results, it could be concluded that TBARS production in normal condition group is very slow and in FeSO4 treated groups, it is very high. Results revealed that at lower doses the rate of formation of TBARS is slow, which increased with dose. Significant and moderate results were found from 0.40 mM to 0.80 mM of ferrous sulphate.